What’s in a name? The effect of congruent and incongruent product names on liking and emotions when consuming beer or non-alcoholic beer in a bar - Silva, Ana Patricia (2017)
This study concerns the expectations, liking and emotions related to the consumption of conventional beer and non-alcoholic beer (NAB), which are related but different products. These beverages are derived from the same raw materials and have undistinguished visual sensory cues. However consumers acknowledge the differences between them in terms of flavour, functional and emotional conceptualisations. Of particular interest here is how prior experience with beer and NAB and the conceptual information this generates in a consumer, can influence his or her response to its consumption in an appropriate setting - a bar. The labelling of a sample as beer or non-alcoholic beer was employed as a prompt to study the effects on liking and emotions provoked, when drinking a beer or a NAB, in a bar. Over 4 sessions, 155 consumers drank a glass of beer or NAB under two different conditions, labelled either correctly or incorrectly with respect to the actual composition of the sample. Questionnaires were used to rate the liking and emotions prior to and after consumption. The naming of NAB as beer significantly increased the liking and changed one emotion towards a positive direction, namely participants felt more fulfilled. When beer was presented as NAB it did not affect the liking but did significantly reduce the intensity of six positive emotions. Participants felt less comforted, exuberant, good, happy, joyful and loving. This study showed that labelling and the conceptual information generated in consumers might influence their response after consumption of these beverages.